EKSEKUSI TERHADAP OBJEK JAMINAN FIDUSIA PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 18/PUU-XVII/2019 DAN BENTUK PERLINDUNGAN HUKUM TERHADAP DEBITUR - Welfiandi, Fitrian (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Fiduciary guarantee is a guarantee right for movable objects both tangible and intangible and immovable, especially buildings that cannot be encumbered with mortgage rights that remain in the possession of the Fiduciary Giver, as collateral for certain repayments that give priority to Fiduciary Recipients over other creditors. After the Constitutional Court Decision Number 18 / PUU-XVII / 2019 resulted in changes to the provisions of Article 15 paragraph (2), Article 15 paragraph (3), and Elucidation of Article 15 paragraph (3) UUJF, specifically changes to the interpretation of breach of fiduciary violations and executions. This thesis will discuss issues regarding the execution of fiduciary security objects after the Constitutional Court ruling No. 18 / PUU-XVII / 2019 and how the legal protection of debtors for arbitrary creditors' actions.Keywords: execution, fiduciary, debtor protection.